Impact of Precision Nutrition on Microbiota and Obesity - Merra, Giuseppe; Gualtieri, Paola; De Lorenzo, Antonino; Capacci, Annunziata; Frank, Giulia; Dri, Maria; Di Renzo, Laura; Marchetti, Marco (Current Nutrition & Food Science, 2024)
The human body is colonized by trillions of microbes, that contribute to our health and well-being. Many factors influence the composition and functions of the intestinal microbiota, including the host's eating habits, which seem to have a significant effect. A healthy intestinal microbiota is essential for proper metabolic function and homeostasis. Alterations in microbial composition could dramatically cause obesity and diabetes, modifying and influencing host metabolism, homeostasis, and central appetite mechanism. Brain reward signaling is mediated by the dopaminergic mesolimbic system and plays an important role in the development of obesity. Dysregulation of the energy balance causes obesity. Obesity is a serious health problem. The composition of the intestinal microbiota influences various aspects of energy metabolism: digestion, food intake from ingested foods, food components, and accumulation of excess fat. Therefore, the microbial community can contribute significantly to the progression of obesity and its complications. A
Keywords: microbiome